Standardization of Keezhanelli chooranam (KNC): A Single-Herbal Siddha Formulation: Soruban T.1* and Sathiyaseelan V.2 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2026)
Standardization of herbal formulations is essential to ensure the quality, safety, and efficacy of traditional medicines. This study aimed to establish standardization parameters for Keezhanelli Chooranam (KNC), a Siddha formulation prepared from Phyllanthus amarus, traditionally used in the management of Madhumegam (diabetes mellitus). KNC was prepared according to classical Siddha methods and analyzed using modern techniques in accordance with AYUSH guidelines. Physicochemical evaluation revealed a brownish, moderately fine powder with characteristic odour, particle size of 94.67 ± 25.5 µm, pH 6.6, and good solubility in water, ethanol, and DMSO. Loss on drying (5.467 ± 0.30%), total ash (0.31 ± 0.026%), extractive values, and absence of acid-insoluble ash were within acceptable limits. ICP-OES analysis confirmed the absence of toxic heavy metals. HPTLC profiling showed multiple phytochemical peaks with Rf values ranging from 0.01 to 0.66. Microbial studies confirmed sterility of the formulation. The results indicate that KNC meets standard quality and safety requirements, supporting its suitability for further pharmacological and clinical evaluation.